Citizens' perception of modern pig production in Germany: a mixed-method research approach. Issue 8 (1st August 2016) - Weible, Daniela; Christoph-Schulz, Inken; Salamon, Petra; Zander, Katrin
Abstract : Purpose: – The wide divergence of the people's expectations and agricultural reality results in conflicts between the agricultural sector and the general public. Contemporary animal husbandry systems are being increasingly critically addressed by media; however, there is no information about peoples' perceptions and attitudes concentrating precisely on specific animal husbandry systems. The purpose of this paper is to explore citizens' perceptions, expectations and main points of criticism in regard to intensive pig production in Germany, and to identify and describe distinct population groups reflecting different attitudes. Design/methodology/approach: – A mixed method approach combining qualitative focus groups with a quantitative online survey has been employed. Focus groups capture a wide variety of opinions and concerns in an exploratory manner. Based on these findings, the quantitative survey ( n =1, 500 citizens) allowed the identification and characterisation of population groups with identical attitudes regarding pig husbandry. Findings: – Qualitative research uncovered a huge range of criticism on pig husbandry, e.g. lack of space, frequency and prophylactic use of medications as well as a lack of care. A relationship was seen between the lack of space, widespread use of medications and behavioural disorders. Consumer preferences for buying cheap meat were believed to be part of the problem since this behaviour fosters the development of larger farms. Quantitative research confirmed the generally critical perception and identified three population groups. Only one third of the population was really concerned about animal husbandry. Younger people and people with better knowledge of agriculture were stronger opponents of intensive pig husbandry. Practical implications: – Results indicate that increasing people's knowledge may have an adverse effect on their acceptance of modern farming systems. More communication and better information strategies will probably not improve societal acceptance by itself. Instead, agricultural production systems need to be improved to meet better consumers' expectations whereas communicating these improvements to consumers and the general public in a well-targeted manner will be required as well. Originality/value: – When considering options for enhancing public acceptance of modern animal husbandry, a combination of different strategies by different stakeholders is needed. The agricultural sector should improve its communication with the general public and rethink its production practices against the background of public expectations. The government and its agencies urgently need to improve monitoring of the compliance of actual production practices with existing laws and to enforce them. Additionally, adjustments of current regulations of animal husbandry in light of public expectations should be considered.